The Effect of Quality of Service and Price on Consumer Satisfaction at Honda Workshop AHASS 07723 Tajur Raya Bogor - Yulianingsih; Gunawan, Rachmat; Prihatini (MultiTech Publisher, 2023)
This study aims to analyze and identify the effect of service quality and price both simultaneously and partially on customer satisfaction at the Honda AHASS 07723 Tajur workshop. The total sample of all consumers is 100 people. The questionnaire was tested with validity tests, reliability tests, and also classic assumption tests. The results of these tests are valid, reliable, and can be used for regression data. The analytical method used in this study is a descriptive and verification method with a quantitative approach. The results showed that the variables of service quality and price both simultaneously and partially had a positive and significant effect on customer satisfaction at the Honda Workshop AHASS 07723 Tajur. The test results for the coefficient of determination (R Square) are 47.8% while the remaining is 52.2%. The relationship between service quality and price is very strong with a correlation coefficient of 0.691.